The value of contrast-enhanced ultrasound in percutaneous biopsy of retroperitoneal masses - Safai Zadeh, Ehsan; Görg, Mathis; Görg, Christian; Prosch, Helmut; Trenker, Corinna; Westhoff, Christina Carolin; Dietrich, Christoph F.; Raab, Nils; Alhyari, Amjad; Huber, Katharina; Pochepnia, Svitlana; Weber, Michael; Findeisen, Hajo (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose To evaluate the diagnostic yield of contrast-enhanced ultrasound (CEUS)-guided biopsy of retroperitoneal masses (RMs).Materials and Methods Between 2006 and 2023, 87 patients presented at our US center for biopsy of an RM. In all biopsies, CEUS was performed prior to the intervention. The technical success rate of biopsy, the presence of diagnostic tissue in solid tumor biopsy samples, the accuracy of the biopsy and the occurrence of post-interventional complications were evaluated.Results A US-guided biopsy could be conducted in 84/87 cases (96.6%). In 3/87 cases (3.4%), US-guided biopsy was impossible because the planned needle path was obstructed by vital structures. Of 84 lesions, 80 (95.2%) were solid lesions, and 4 (4.8%) were lesions containing fluid. In all solid tumors, 80/80 (100%), diagnostic vital tissue was successfully obtained. CEUS-guided biopsy showed a sensitivity of 93.2%, a specificity of 100%, a positive predictive value of 100%, a negative predictive value of 72.2%, and a diagnostic accuracy of 94.2% for the differentiation between malignant and benign RMs. In one of the 84 cases (1.2%), there was a complication of postinterventional abdominal pain.Conclusion Percutaneous CEUS-guided biopsy is a safe procedure with a high diagnostic yield and a low complication rate.
Keywords: ultrasound; retroperitoneal masses; CEUS; biopsy; intervention